Decoupling of microbial community dynamics and functions in Arctic peat soil exposed to short term warming - Yang, Sizhong; Liebner, Susanne (Jun.-Prof. Dr.); Svenning, Mette Marianne; Tveit, Alexander Tøsdal (Molecular Ecology, 2021)
Temperature is an important factor governing microbe-mediated carbon feedback from permafrost soils. The link between taxonomic and functional microbial responses to temperature change remains elusive due to the lack of studies assessing both aspects of microbial ecology. Our previous study reported microbial metabolic and trophic shifts in response to short-term temperature increases in Arctic peat soil, and linked these shifts to higher CH4 and CO2 production rates (Proceedings of the National Academy of Sciences of the United States of America, 112, E2507-E2516). Here, we studied the taxonomic composition and functional potential of samples from the same experiment. We see that along a high-resolution temperature gradient (1-30 degrees C), microbial communities change discretely, but not continuously or stochastically, in response to rising temperatures. The taxonomic variability may thus in part reflect the varied temperature responses of individual taxa and the competition between these taxa for resources. These taxonomic responses contrast the stable functional potential (metagenomic-based) across all temperatures or the previously observed metabolic or trophic shifts at key temperatures. Furthermore, with rising temperatures we observed a progressive decrease in species diversity (Shannon Index) and increased dispersion of greenhouse gas (GHG) production rates. We conclude that the taxonomic variation is decoupled from both the functional potential of the community and the previously observed temperature-dependent changes in microbial function. However, the reduced diversity at higher temperatures might help explain the higher variability in GHG production at higher temperatures.